THE INFLUENCE OF RENEWABLE ENERGY POLICY ON BUSINESS LAW AND NATURAL RESOURCES - Sirait, Putri Indriani (Communale Journal, 2024)
The impact of renewable energy policies on business law and natural resources is the main focus of this research. With increasing awareness of climate change and the need to reduce carbon emissions, governments worldwide, including Indonesia, have enacted policies to promote the use of renewable energy. These policies affect the energy sector and significantly affect business law and natural resource management. This study explores the impact of renewable energy policies on business regulation, including changes in licensing regulations, fiscal incentives, and environmental responsibilities. Furthermore, it discusses how these policies affect natural resource management, particularly conservation and land use. Through literature analysis and case studies, this research provides insights into how renewable energy policies can be effectively implemented to achieve sustainability goals without neglecting economic and social interests.